NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIASuccessful use of cidofovir to treat refractory cytomegalovirus infection in heart transplant recipient – a case report - Krynicka-Mazurek, Anna; Zakliczyński, Michał; Nożyński, Jerzy; Przybylski, Roman; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Cytomegalovirus (CMV) infection poses a serious risk to patients after organ transplantation. It affects not only the early postoperative period, but through indirect effects contributes to shortening the long-term survival. CMV infection typically occurs within the period from the 2nd to the 6th month after organ transplantation. CMV infection that presents after 6 months is described as late CMV disease. Late onset CMV infection may present in an atypical way; therefore the diagnosis of CMV disease should be taken into consideration at any time after transplantation. In this article we present a clinical case of atypical CMV infection in a patient after orthotopic heart transplantation. It was unusual because of the timing and because of the lack of characteristic signs and symptoms. We also describe our experiences with cidofovir, a second-line antiviral drug, which is rarely used in patients after solid organ transplantation.